UPAYA PENINGKATAN PEMAHAMAN SISWA MELALUI PEMBELAJARAN BERBASIS EKSPERIMEN PADA MATERI SIFAT - SIFAT BENDA DIKELAS 5 SEKOLAH DASAR - Sari, Lika Tunjung; Tryanasari, Dewi; Jatmikawati, Melina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study seeks to assess the efficacy of employing the experimental method to enhance students' comprehension and academic outcomes regarding object properties in 5th-grade education. The experimental method serves as an alternative instructional strategy, enabling students to directly engage with scientific concepts through hands-on experiments. The research was conducted over two cycles, implementing the experimental method. In the initial cycle, results indicated that the majority of students had not attained mastery of the subject, with the class averaging a score of only 4.3. This suggests that traditional teaching methods may not fully accomplish the desired educational objectives. However, following the second cycle and the integration of the experimental method, there was a notable enhancement in students' comprehension and academic achievements. Approximately 82% of students reached mastery level, leading to a class average score increase to 6.2. These findings underscore the effectiveness of the experimental method in fostering active student participation in the learning process. By immersing students in practical experiments, they can develop a deeper grasp of scientific principles. Moreover, this hands-on approach bolsters students' motivation as they witness the real-world applications of their classroom learning. These outcomes make significant contributions to refining instructional strategies for teaching object properties to 5th-grade students.